Pengaruh Penggunaan Media Pembelajaran Powerpoint Interaktif Terhadap Minat Belajar Matematika Siswa Kelas VII Madrasah Tsanawiyah - Hermawan, Toto; Khairiani, Dian; Muthmainnah, Muthmainnah; Saifullah, Iman; Bisri, Hasan (Universitas Cokroaminoto Yogyakarta, 2024)
This research aims to determine the effect of using interactive PowerPoint learning media on students' interest in learning mathematics. The population of this study was class VII students of Madrasah Tsanawiyah. Of the 3 existing classes, 2 classes were taken using the Random Sampling technique as samples, with one class as the experimental class and one class as the control class. This research uses the Quasi Experiment method with Nonequivalent Control Group Design. Treatment in the experimental class was given using interactive PowerPoint learning media, while in the control class learning was carried out conventionally using textbooks and LKS learning media. The results of the research show that there is an influence on interest in learning mathematics on students who use interactive PowerPoint learning media in experimental classes. This is proven by the results of observations of interest in learning of 81.60%. Inferential statistics using the t-test formula, obtained a tcount value of 13.30 which is greater than ttable with a value of 1.99 at a significance level of 5%. This shows that the null hypothesis is rejected and the alternative hypothesis is accepted